Benign neuromyelitis optica is rare in Japanese patients. (August 2015) - Uzawa, Akiyuki; Mori, Masahiro; Muto, Mayumi; Uchida, Tomohiko; Masuda, Hiroki; Masuda, Saeko; Kuwabara, Satoshi
Good-outcome neuromyelitis optica (NMO) is defined as an Expanded Disability Status Scale (EDSS) score of ≤3.0 at 10 years after onset. The clinical courses of 80 consecutive patients with NMO were analyzed to identify the frequency and features of Japanese patients with good-outcome NMO. Of the 80 patients, 37 had a disease duration of >10 years; of these, eight (21.6%) presented a good outcome. These cases presented lower EDSS scores during the early phase of disease compared with those with conventional NMO. However, half of these patients developed severe disabilities later on, indicating that truly benign NMO is rare.